Microtus agrestis - Mathias, Maria Da Luz; Hart, E. Blake; Ramalhinho, Maria Da Graca; Jaarola, Maarit (Zenodo, 2017)
Microtus agrestis (Linnaeus, 1761) Field Vole Mus agrestis Linnaeus, 1761:11. Type locality “Svecia [= Sweden],” Uppsala. Mus gregarius Linnaeus, 1766:84. Type locality “ Germania, Svecia [= Germany and Sweden],” East Prussia. Mus arvalis nigricans Kerr, 1792:239. Replacement name for Mus agrestis Linnaeus, 1761. Arvicola hirta Bellamy, 1839:373. Type locality “Yealmpton,” Devonshire, England. Arv. [ icola ] Bailloni de Sélys Longchamps, 1841:225. Type locality “Abita il Nord della Francia e della Svizzera [=Inhabits the North of France and Switzerland.” Arvicola neglecta Jenyns, 1841:270. Type locality “Megarnie Castle in Perthshire,” Scotland. Arvicola levernedii Crespon, 1844:73. Type locality “entre St-Gilles et Aiguesmortes [= between St. Gilles and Aiguesmortes],” Gard, France. Lemmus insularis Nilsson, 1844:34. Type locality “Ostgötha, skärgård,” Sweden. A. [ rvicola ] britannicus de Sélys Longchamps, 1847:307. Type locality “L’Angleterre et l’Écosse [= England and Scotland].” Arvicola rozianus Bocage, 1865:7. Type locality “ Coimbra, no sitio da Geria,[= Coimbra, county of Geria],” Portugal. Arvicola agrestis var. nigra Fatio, 1869:241. Type locality “près d’Engstlen [= vicinity of Engstlen],” Berne, Switzerland. [ Arvicola agrestis var. ] rufa Fatio, 1900:472. Type locality “dans les Alpes savoisiennes, frontière du Valais, et dans les Alpes vaudoises (aux plans de Frenières),” Geneva, Switzerland. Arvicola agrestis angustifrons Fatio, 1905:191. Type locality “près de Zermatt, entre 1620 et 1700 m. s/m., en Valais [= near Zermatt between 1,620 and 1,700 meters in Valais],” Switzerland. Arvicola agrestis latifrons Fatio, 1905:194. Type locality “sur quelques points en Suisse, dans les bois de Veyrier, près de Geneve; entre autres et dans les environs de Lucerne [= at some points in Switzerland, in the woods of Veyrier near Geneva; including in and around Lucerne].” Microtus agrestis exsul Miller, 1908:201. Type locality “North Uist, Hebrides,” Scotland. Microtus agrestis insul Lydekker, 1909:74. Incorrect subsequent spelling of Lemmus insularis Nilsson, 1844. Microtus agrestis mongol Thomas, 1911:759. Type locality “Kemtchik Valley, Tannu-ola Mts., N.W. Mongolia.” Microtus agrestis arcturus Thomas, 1912:398. Type locality “Barlik Mts. S., N.W. Dzungaria,” China. Microtus agrestis mial Barrett-Hamilton and Hinton, 1913a:364. Type locality “Eigg, Inner Hebrides,” Scotland. Microtus agrestis luch Barrett-Hamilton and Hinton, 1913a:366. Type locality “Muck, Inner Hebrides,” Scotland. Microtus agrestis macgillivrayii Barrett-Hamilton and Hinton, 1913b:831. Type locality “Islay,” Inner Hebrides, Scotland. Microtus agrestis fiona Montagu, 1922:940. Type locality “Gigha,” Inner Hebrides, Scotland. Microtus agrestis punctus Montagu, 1923:868. Type locality “ Bled, Slovenia.” Microtus hirtus orioecus Cabrera, 1924:8. Type locality “Molins, Montseny, Prov. Gerona,” Spain. Microtus agrestis pannonicus Ehik, 1924:76. Type locality “Orman, near Komarviros County Zala, Hungary.” Microtus agrestis tridentinus Dal Piaz, 1924:10. Type locality “Brennero, Alto Adige, 1400 m s/m,” Italy. Microtus agrestis estiae Reinwaldt, 1927:13. Type locality “Inseln Villsandi und Abruka, [= Villsandi and Abruka Islands],” Estonia. Microtus agrestis Wettsteini Ehik, 1928:197. Type locality “Ob. Trixen, Karintia [= Carinthia],” Austria. Microtus agrestis ognevi Skalon, 1935:11. Type locality “Церковенское на р. Таз [=Tserkovenskoe on Taz River],” northwestern Siberia. Microtus agrestis pallida Melander, 1938:74. Type locality “Смоленская обл, Ельнинский р- н. [= Elninsky department of Smolensk province, near vill. Miloje],” Russia. Microtus agrestis argyropoli Ognev, 1944:179. Type locality “South Urals, Valley of Inzer River,” Russia. Microtus agrestis scaloni Heptner, 1948:710. Replacement name for Microtus agrestis ognevi Skalon, 1935. Microtus agrestis argyropuli Ognev, 1950: Replacement name for Microtus agrestis argyropoli Ognev, 1944. Microtus agrestis carinthiacus Kretzoi, 1958:57. Replacement name for M. a. wettsteini Ehik, 1928. Microtus agrestis enez-groezi Heim de Balsac and de Beaufort, 1966:638. Type locality “Groix (= Morbihan),” France. Microtus agrestis armoricanus Heim de Balsac and de Beaufort, 1966:638. Type locality “environs de Quimper (= Finistère),” France. CONTEXT AND CONTENT. Order Rodentia, suborder Myomorpha, superfamily Muroidea, family Cricetidae, subfamilyArvicolinae, genus Microtus , subgenus Microtus . There remains some uncertainty concerning valid subspecies. Musser and Carleton (2005) list the above 39 named forms of Microtus agrestis without reference to subspecies. NOMENCLATURAL NOTES. Microtus agrestis and the Nearctic M. pennsylvanicus are similar morphologically (Klimkiewicz 1970). However, this similarity represents convergence, not a phylogenetic relationship (Krapp and Niethammer 1982; Musser and Carleton 2005). Phylogenetic analyses based both on karyotypes (Modi 1987) and DNA sequences of the entire cytochrome -b gene (Conroy and Cook 2000; Jaarola et al. 2004) clearly show that M. agrestis and M. pennsylvanicus are separate species. The European populations of M. agrestis are differentiated as 3 evolutionary units that may represent cryptic species (Kryštufek et al. 2008; Paupério et al. 2012). The generic name Microtus is a combination of 2 Greek words, micros for small and ous for ear, and the specific epithet agrestis is a Latin word meaning “of the field.” Vernacular names assigned to M. agrestis include common field vole, grass mouse, short-tailed vole, dark vole, blackish meadow mouse, and shorttailed field mouse (Alibhai and Gipps 1991; MacDonald and Barrett 1993; Kryštufek et al. 2008). DIAGNOSIS Juvenile Microtus agrestis , the common vole ( M. arvalis ), the root vole ( M. oeconomus ), and the East European vole ( M. levis —formerly M. rossiaermeridonalis ) are virtually indistinguishable by gross morphology (Nekrutenko et al. 2000). Representational difference analysis was used to isolate species-specific markers—Mag3 for M. agrestis and Moe1 for M. oeconomus (Nekrutenko et al. 2000). Using these sequences, species-specific polymerase chain reaction (PCR) primers produced unique amplification products that were able to distinguish between these 2 species. Microtus agrestis (Fig. 1) can be characterized by its pelage, rather long, shaggy, grayish brown, often tinged with russet and by its bicolored tail with dark dorsal fur. Tail length is about one-third the length of head and body. Only M. duodecimcostatus and M. lusitanicus have shorter tail lengths. These characters of M. agrestis combined with some or all (depending on which comparison is being made) of the following are diagnostic of the species: skull moderately broad, with width> one-half the length; width of interorbital constriction> 3.3 mm; M2 with 3 inner ridges ≤ 5 fields: an anterior loop, 2 outer and 1 inner closed triangles, a character absent in other European vole species, and a 5th field in a postero-internal position; M3 with 5 fields: an anterior loop, 3 closed triangles, and a long terminal loop rarely simplex; m1 with ≥ 7 fields and 4 outer ridges on the outer side; m3 with 3 transverse fields; length of upper molar toothrow never> 7 mm; foramen mandibulare usually lying over protuberance of lower incisor (Miller 1912; Ellerman 1940; Reichstein 1959; Saint-Girons 1973; Corbet 1978; Krapp and Niethammer 1982). Microtus agrestis is very similar to M. arvalis , but the latter can be distinguished by its pelage that is more yellowishbrown and its slightly smaller size (body length of M . arvalis 90–120 mm, body weight 14–40 g—Krapp and Niethammer 1982; MacDonald and Barrett 1993). Hairs inserted near the base of the ear are shorter in M. arvalis than M. agrestis (Dienske 1969). The asynaptic X and Y chromosomes of M. agrestis contain additional, nonobligatory heterochromatic blocks not found in another species of asynaptic vole, the Mediterranean pine vole ( M. duodecimcostatus ) as addressed by Borodin et al. (1995). GENERAL CHARACTERS General form of Microtus agrestis is robust with a large head (broad posteriorly), short and rounded ears, small eyes with diameter of 3.1–3.8 mm (Krapp and Niethammer 1982), and blunt snout. Mouth is small with upper incisors projecting very slightly. Tail is scantily covered with hair and has as many as 20 visible rings per cm near middle (Miller 1912; Krapp and Niethammer 1982). Ears are mostly covered by fur; meatal lobe (length) is frequently> l mm though <2 mm (Dienske 1969). General color of dorsum varies from dark gray-brown to chestnut-brown, with underparts pure gray or pale brown (Corbet and Harris 1991; MacDonald and Barrett 1993; Mathias 1999). Juveniles are darker than adults. M. agrestis has 2 pairs of pectoral and 2 pairs of inguinal mammae. Hind feet have 6 plantar pads, whereas forefeet have 5 palmar pads and inner digit is reduced to a minute tubercle (Miller 1912). Dorsal profile of skull is moderately convex. Condyles are visible in dorsal view due to forward projection of occiput (Fig. 2). In older animals, outer edges of parietals have welldeveloped longitudinal ridges that are continuous posteriorly with lambdoidal crest and which come together abruptly anteriorly to join interorbital ridge (Miller 1912). Auditory bullae are large and evenly inflated. Interorbital region is narrow, subcylindrical, and has distinct temporal ridges, which can unite to form a definite median crest extending well forward to nasals (Magalhães and Madureira 1980). Nasals are broad anteriorly and abruptly narrow at middle; posterior end is pointed, blunt, or angular. Incisive foramen is long and narrow, extending approximately to molar alveoli. Well-developed postorbital processes are present (Magalhães and Madureira 1980). Posterior edge of foramen mandibulare is about 0.5 mm from posterior edge of mandible (Dienske 1969; Fedyk and Ruprecht 1971). Mandible is robust and masseteric ridge is well developed. Lower incisors are much less strongly curved than upper incisors. Molar teeth are open-rooted throughout life, decreasing in size posteriorly. A postero-internal loop is present in M1, similar to that in M2; this is a frequent character in some populations (morphotype exsul — Miller 1912; Ognev 1950; Niethammer 1964; Reichstein and Reise 1965; Reichstein 1966; Meylan 1967; Almaça 1993; Yalden 1999). An 8th field in an anterior position can also occur in M1 (Dienske 1969; Magalhães and Madureira 1980). Marked geographical variation is found in size and color patterns of M. agrestis . M . agrestis from northern Europe (Scotland, Scandinavia, northern Russia), the Alps, and Camargue (France) are larger than those from central Europe (Krapp and Niethammer 1982). In England (Alibhai and Gipps 1991) and Sweden (Hansson and Jaarola 1989) size increases from south to north. Size also varies with elevation; larger M . agrestis are present at higher elevations in the area that was formerly Czechoslovakia (Krapp and Niethammer 1982) and in France and Portugal (Almaça 1993). Individuals with darker dorsal pelage occur in Scandinavia and Scotland, and individuals with lighter pelage are found in central Europe, southern England, and northernmost Scandinavia (Corbet and Southern 1977; Krapp and Niethammer 1982). Microtus agrestis males average slightly larger than females in external and cranial measurements in some populations (Reichstein 1959; Krapp and Niethammer 1982), but exhibit little or no secondary sexual variation in size in other populations (Wasilewski 1956; Gebczynska 1964; Saint-Girons 1973; Alibhai and Gipps 1991). Selected ranges of external and cranial measurements (mm; sexes combined) for adult M. agrestis from England (E, n = 38–46), France (F, n = 51–93), the Netherlands (N, n = 58), Switzerland (S, n = 17), and Portugal (P, n = 3–33) were: length of body, 115.0–121.0 (E), 85.0–130.0 (F), 78.0– 123.0 (S); length of tail, 25.0–46.0 (F), 29.5–46.0 (S); length of hind foot, 17.0–17.4 (E), 15.0–21.0 (F), 17.0–20.0 (S); length of ear, 9.0–14.0 (F), 10.0–13.0 (S); condylobasal length, 25.2–26.1 (E), 22.8–27.9 (F), 24.1–27.4 (S), 24.7–25.9 (P); zygomatic breadth, 12.1–15.7 (F), 12.1–16.1 (S), 12.6–14.1 (P); width of interorbital constriction, 3.1–3.9 (F), 3.3–3.8 (S), 2.3–3.2 (P); length of nasals, 5.5–7.8 (S), 5.9–7.0 (P); palatal length, 10.6– 15.0 (N); length of maxillary toothrow, 5.3–6.9 (F), 4.5–6.9 (N), 5.4–6.7 (S), 5.0–6.3 (P); length of mandibular toothrow, 5.2–6.7 (F), 5.4–6.6 (S), 5.0–5.8 (P); length of mandible, 12.4–17.0 (N), 14.0–17.3 (S), 13.6–15.9 (P—Dienske 1969; Saint-Girons 1973; Magalhães and Madureira 1980; Krapp and Niethammer 1982; Alibhai and Gipps 1991). Ranges of cranial measurements (mm; sexes combined) of 26 M. a. levernedii (l) from Switzerland and France (Madureira 1983), 13 M. a. agrestis (a) from Norway and Sweden (Miller 1912), and 3 M. a. neglectus (n) from Scotland (Miller 1912) were: condylobasal length, 26.6–28.4 (a), 25.0–25.4 (n); zygomatic breadth, 15.2–16.8 (a), 14.4–14.4 (n); width of interorbital constriction, 2.6–3.3 (l), 3.4–4.0 (a), 3.2–3.4 (n); width of postorbital constriction, 3.3–3.7 (l); nasal length, 7.2–8.0 (a), 6.8– 7.0 (n); palatal width, 1.5–1.8 (l); length of maxillary toothrow, 6.4–7.0 (a), 6.4–6.6 (n); length of mandibular toothrow, 6.2–6.8 (a), 6.2–6.4 (n); length of mandible, 14.9–17.6 (l), 16.8–18.0 (a), 15.4–16.2.(n). Cranial measurements (mm) of the type specimens of M. a. levernedii from Gard, France (female), and M. a. nigra (or niger ) from Berne (Geneva), Switzerland (male), respectively, were: condylobasal length, 28.0, 26.0; zygomatic breadth, 16.0, 14.8; width of interorbital constriction, 3.6, 3.4; nasal length, 8.0, 7.2; length of maxillary toothrow, 7.2, 6.4; length of mandibular toothrow, 7.0, 6.4; mandible length, 18.0, 16.6 (Miller 1912). Ranges of body and cranial measurements from specimens collected in Europe were: length of head and body, 78–135 mm; length of tail, 18–49 mm (ca. 30% head-body length); length of hind foot, 16–20.5 mm, body mass 14–50 g (birth mass ca. 2 g); condylobasal length, 23–29 mm (sample sizes not given—MacDonald and Barrett 1993). Ranges of body measurements for individuals collected in Spain were: head and body length, 95–123 mm; length of tail, 25–44 mm; length of hind foot, 16–21 mm, mass 21–41 g (sample sizes not given— Gosalbez and Luque-Larena 2002). Mean measurements (mm ± SD ) for footprints of 25 M. agrestis were: forefoot print, 7.0 ± 0.7 in width and 7.6 ± 0.5 in length; hind foot print, 7.0 ± 1.0 in width and 9.1 ± 0.8 in length (van Apeldoorn et al. 1993). Baculae (os penis) measurements (mm) of 2 adult males were: corpus length, 3.5, 3.2; basal width, 0.5, 0.4 (Didier 1954). DISTRIBUTION Distribution of Microtus agrestis (Fig. 3) in northern and central Europe extends from Scandinavia to the Alps, Pyrenees, Galicia, and northern Portugal and from England, Scotland, and nearby small islands eastward to former Yugoslavia, southern Urals, Altai Mountains (Mongolia), northwest China, and Lake Baikal (Russia) regions (Miller 1912; Ognev 1944; Corbet 1978; Krapp and Niethammer 1982; Brunet-Lecomte 1991; Gromov and Plyakov 1992; Mitchell-Jones et al. 1999; Musser and Carleton 2005). The species is absent from Iceland and Ireland (Kryštufek et al. 2008). The morphotype M. a. exsul comprises over 50% of specimens taken from the northern area of Russia, Scandinavia, and Scotland. In central Europe, the M. a. exsul type decreases to about 5%, and in southern Europe and the Alps, it never exceeds 20% of specimens collected (Krapp and Niethammer 1982). FOSSIL RECORD The 1st known fossil remains of Microtus agrestis are from the Upper Pleistocene of Europe (Kurtén 1968). Earlier records are mostly presented as the “ arvalis-agrestis ” group because these 2 species are only differentiated by M2, missing in most of the materials found. In the British Isles, M. agrestis is present from the Cromerian interglacial and Wolstonian period (penultimate glaciation) but never reached Ireland (Alibhai and Gipps 1991; Yalden 1999). Subfossil teeth collected from the island of Jura, Inner Hebrides, between 1,500 and 2,500 years ago, show a progressive simplification of the M1 pattern since that time (Corbet 1975). The M. agrestis group (including M. agrestoides ) was present in the Middle Terrace stage, then absent until the Iglitham stage of the Late Pleistocene (Hinton 1926). Two geochronological forms from France were M. agrestis jansoni with larger size measurements of M 1 in the Middle Pleistocene and M. agrestis aubinensis with smaller size measurement values of M 1 in the Upper Pleistocene (Chaline 1972). In Portugal, M. agrestis is found in Upper Pleistocene deposits of Caldeirão Cave in the center of the country (Póvoas et al. 1992). In southern Poland, fossil remains of M. agrestis indicate that the species was present during the entire late Quaternary, including the Last Glacial Maximum (Nadachowski 1984, 1989, 2001). Other fossils of M. agrestis are reported from Germany, Austria, Hungary, and Bulgaria (Chaline 1972, 1974; Krapp and Niethammer 1982; Nadachowski 1984; Kolfschoten 1994), Hungary (Jánossy 1986), southern Italy (Capasso-Barbato and Gliozzi 2001), and Eastern Europe including the : Published as part of Mathias, Maria Da Luz, Hart, E. Blake, Ramalhinho, Maria Da Graca & Jaarola, Maarit, 2017, Microtus agrestis (Rodentia: Cricetidae), pp. 23-39 in Mammalian Species 49 (944) on pages 23-34, DOI: 10.1093/mspecies/sex003, http://zenodo.org/record/4683692 : {"references": ["LINNAEUS, C. 1761. Fauna Suecica. 2 nd ed. Laurentii Salvii, Stockholm, Sweden.", "LINNAEUS, C. 1766. Systema naturae per regna tria naturae, secundum classes, ordines, genera, species, cum characteribus, differentiis, synonymis, locis. Edition duodecima, reformata. Laurentii Salvii, Stockholm, Sweden.", "KERR, R. 1792. The animal kingdom, or zoological system, of the celebrated Sir Charles Linnaeus; Class I. Mammalia: containing a complete systematic description, arrangement, and nomenclature, of all the known species and varieties of the Mammalia, or animals which give suck to their young; being a translation of that part of the Systema Naturae, as lately published, with great improvements, by Professor Gmelin of Geottingen. J. Murray and R. Faulder, London, United Kingdom.", "BELLAMY, J. C. 1839. Arvicola hirta. The natural history of South Devon. Yealmpton, Devonshire, England, United Kingdom.", "DE SeLYS LONGCHAMPS, E. D. 1841. Arvicola agrestis. Atti della Seconda. Riunione degli Scienziati Italiani, Torino [dated 1840, but published 1841].", "JENYNS, G. L. 1841. Notes on some of the smaller British Mammalia, including the description of a new species of Arvicola, found in Scotland. Annals and Magazine of Natural History, Series 1 7: 261 - 276.", "CRESPON, J. 1844. Faune Meridionale ou description de tous les animaux vertebres vivans et fossiles, sauvages ou domestiques qui se rencontrent toute l'annee ou quine sont que de passage dans la plus grande partie du mididella de la France. Survix d'une methode de taxidermie ou l'art d'empailler les oiseaux. M. Lebrun, Montpelier, France.", "NILSSON, S. 1844. Ofversigt of Kongl Vetensk. Kungliga Vetenskapliga Akadademins Forhandlingar, Ostgotha, Skargard, Stockholm, Sweden.", "DE SeLYS LONGCHAMPS, E. D. 1847. Distribution geographique des Campagnola (Arvicola en Europe). Revue Zoologique 10: 305 - 315.", "BOCAGE, B. D. 1865. Noticia acerca dos Arvicolas de Portugal. Memorias da Academia Real de Sciencias de Lisboa, N. S., III, Pt. 2.", "FATIO, V. 1869. Faune des vertebres de la Suisse. Histoire naturelle des mammiferes (H. Geirg Ligrairep, ed.). Engstlen, Berne, Switerzland.", "FATIO, V. 1900. Deux petits vertebres nouveaux pour la Suisse. Revue Suisse de Zoologie 8: 472.", "FATIO, V. 1905. Liste preliminaire de mammiferes, en vue d'un supplement general a la faune des vertebras de la Suisse. Archives des Sciences Physiques et Naturelles, Geneve, 4 Series 19: 191 - 194.", "MILLER, G. S. 1908. New European voles (from North Uist, Hebrides, Scotland). Annals and Magazine of Natural History, Series 8: 201.", "LYDEKKER, R. 1909. Microtus agrestis insul. Zoological Record, Mammals 45: 74 [dated 1908, but published in 1909].", "THOMAS, O. 1911. New mammals from central and western Asia, mostly collected by Mr. Douglas Caruthers. Annals and Magazine of Natural History, Series 8 8: 758 - 762.", "THOMAS, O. 1912. On mammals from central Asia, collected by Mr. Douglas Caruthers. Two new Asiatic Voles. Annals and Magazine of Natural History, Series 8 9: 391 - 408.", "MONTAGU, I. G. S. 1922. On a further collection of mammals from the Inner Hebrides. Proceedings of the Zoological Society of London 1922: 929 - 941.", "MONTAGU, I. G. S. 1923. On some mammals from Jugoslavia. Proceedings of the Zoological Society of London 1923: 865 - 870.", "CABRERA, A. 1924. Sobre alguns Microtinae de Cataluna. Publicaciones de la Junta de Ciencies Naturals de Barcelona, Trabajos del Museo Ciencias Naturales de Barcelona 7: 1 - 20.", "EHIK, J. 1924. Preliminary description of a new Microtus agrestis from Hungary. Annales Musei Nationalis Hungarici 21: 76.", "DAL PIAZ, G. B. 1924. Studio sulle Arvicole Tridentine. Publication by the Curator of the Civic Museum of Trento. Studi Trentini 4: 1 - 17.", "REINWALDT, E. R. 1927. Uber Verbreitung und Schutz einiger Saugtiere Estlands nach Daten einer Enquete der Naturschutzsektion der Universitat Tartu (Dorpat) no 10. Published by Edwin Reinwaldt (Ed: Bergmann), Truckerei, Tautu, Estonia.", "EHIK, J. 1928. Einige daten zur saugetierkunde ungarns. Annales Musei Naationalis Hungarici 25: 197.", "SKALON, V. N. 1935. Microtus agrestis ognevi. Izvestiya Gosudarstvennogo Protivochumnogo Instituta II: 44 - 45.", "MELANDER, V. A. 1938. Microtus agrestis pallida. Opredeliitel' mlekopitayushchikh Smolenskoi i smezhnykh oblastei (Key to mammals of Smolensk and adjacent regions [Elnya County, former Smolensk Province]).", "OGNEV, S. I. 1944. Contribution to the taxonomy of Palearctic Microtine. Doklady Akademii Nauk SSSR 43: 177 - 190.", "HEPTNER, V. G. 1948. On the nomenclature of some mammals. Doklady Akademiia Nauk SSSR 60: 709 - 712.", "OGNEV, S. I. 1950. Mammals of the USSR and adjacent countries. Rodents, Izdatel'stvo Akademii Nauk SSSR, Moskva-Leningrad, Volume 7. English Translation: Israel Program for Scientific Translations, Jerusalem, Israel, 1964.", "KRETZOI, M. 1958. New names for Arvicolid homonyms. Annales Historico- Naturales Musei Nationalis Hungarici 50: 55 - 58.", "KLIMKIEWICZ, H. K. 1970. The taxonomic status of the nominal species Microtus pennsylvanicus and Microtus agrestis (Rodentia, Cricetidae). Mammalia 64: 640 - 665.", "MODI, W. S. 1987. Phylogenetic analyses of chromosomal banding patterns among the Nearctic Arvicolidae (Mammalia: Rodentia). Systematic Zoology 36: 109 - 136.", "JAAROLA, M., AND J. B. SEARLE. 2004. A highly divergent mitochondrial DNA lineage of Microtus agrestis in southern Europe. Heredity 92: 228 - 234.", "KRYsTUFEK, B., V. VOHARALiK, J. ZIMA, AND I. ZAGORODNYUK. 2008. Microtus agrestis. The IUCN Red List of Threatened Species: e. T 13426 A 3927248.", "PAUPeRIO, J., J. S. HERMAN, J. MELO- FERREIRA, M. JAAROLA, P. C. ALVES, AND J. B. SEARLE. 2012. Cryptic speciation in the field vole: a multilocus approach confirms three highly divergent lineages in Eurasia. Molecular Ecology 21: 6015 - 6032.", "NEKRUTENKO, A., K. D. MAKOVA, AND R. J. BAKER. 2000. Isolation of binary species-specific PCR-based markers and their value for diagnostic applications. Gene 249: 47 - 51.", "MILLER, G. S. 1912. Catalogue of the mammals of western Europe (Europe exclusive of Russia) in the collection of the British Museum. British Museum (Natural History), London, United Kingdom.", "ELLERMAN, J. R. 1940. The families and genera of living rodents. I. Family Muridae. British Museum (Natural History), London, United Kingdom.", "REICHSTEIN, H. 1959. Populationsstudien an Erdmausen, Microtus agrestis L. (Markierungsversuche). Zoologische Jahrbucher (Systematik) 86: 367 - 382.", "CORBET, G. B. 1978. The mammals of the Palearctic region: a taxonomic review. British Museum (Natural History), London, United Kingdom.", "DIENSKE, H. 1969. Notes on differences between some external and skull characters of Microtus arvalis (Pallas, 1778) and Microtus agrestis (Linnaeus, 1761). Zoologische Mededelingen 44: 83 - 107.", "BORODIN, P. M., O. V. SABLINA, AND M. I. RODIONOVA. 1995. Pattern of X-Y chromosome pairing in microtine rodents. Hereditas 123: 17 - 23.", "MATHIAS, M. L. 1999. Mamiferos Terrestres de Portugal Continental, Acores e Madeira. Instituto da Conservacao da Natureza, Lisboa, Portugal.", "NIETHAMMER, J. 1964. Ein Beitrag zur Kenntnis der Kleinsauger Nordspaniens. Zeitschrift fur Saugetierkunde 29: 193 - 220.", "REICHSTEIN, H. 1966. Abweichendes Molaren-Schmelzchlingenmuster am M 1 beieiner Erdmaus Microtus agrestis (L.). Zeitschrift fur Saugetierkunde 31: 480 - 481.", "MEYLAN, A. 1967. Les petits mammiferes terrestres du Valais central (Suisse). Mammalia 31: 225 - 245.", "ALMAcA, C. 1993. On the Portuguese population of Microtus agrestis (Linnaeus, 1761). Arquivos do Museu Bocage Novo Serie 2: 319 - 335.", "YALDEN, D. 1999. The history of British mammals. Poyser, London, United Kingdom.", "WASILEWSKI, W. 1956. Untersuchungen uber die morphologische Veranderlichkeit der Erdmaus (Microtus agrestis Linne). Annales Universitatis Mariae Curie-Sklodowska (C) 9: 261 - 305.", "GEBCZYNSKA, Z. 1964. Morphological changes occurring in laboratory Microtus agrestis with age. Acta Theriologica 9: 67 - 79.", "MADUREIRA, M. L. 1983. On the identification of west-European Microtus of the sub-genera Microtus and Chionomys (Mammalia, Rodentia). A principal component analysis. Revista de Biologia 12: 615 - 632.", "VAN APELDOORN, R., ET AL. 1993. Footprints of small mammals. A field method of sampling data for different species. Mammalia 57: 407 - 422.", "DIDIER, R. 1954. Etude systematique de l'os penien des mammiferes (suite). Rongeurs: murides. Mammalia 18: 237 - 256.", "CORBET, G. B. 1975. Finding and identifying mammals in Britain. British Museum (Natural History), London, United Kingdom.", "HINTON, M. A. C. 1926. Monograph of the voles and lemmings (Microtinae) living and extinct. British Museum of Natural History I: 131; 583.", "CHALINE, J. 1972. Les rongeurs du Pleistocene moyen et superieur de France. Cahiers de Paleontologie. Editions du Centre National de la Recherche Scientifique, Paris, France.", "PoVOAS, J., J. ZILHAO, J. CHALINE, AND P. BRUNET- LECOMTE. 1992. La faune de rongeurs du Pleistocene superieure de la grotto de Caldeirao (Tomar, Portugal). Quaternaire 3: 40 - 47.", "NADACHOWSKI, A. 1984. Morphometric variability of dentition of the Late Pleistocene voles (Arvicolidae, Rodentia) from Bacho Kiro Cave (Bulgaria). Acta Zoologica Cracoviensia 27: 149 - 176.", "NADACHOWSKI, A. 1989. Origin and history of the present rodent fauna in Poland based on fossil evidence. Acta Theriologica 34: 37 - 53.", "NADACHOWSKI, A. 2001. New important neogene and Pleistocene mammals assemblages from Poland. Bolletino della Societa Paleontologica Italiana 40: 243 - 248.", "CHALINE, J. 1974. Esquisse de l'evolution morphologique, biometrique et chromosomique du genre Microtus (Arvicolidae, Rodentia) dans le Pleistocene d l'hemisphere nord. Bulletin de la Societe Geologique de France, Series 7 16: 440 - 450.", "KOLFSCHOTEN, T. Van. 1994. Small mammals from the early Mesolithic site of Bedburg-Konigshoven, Germany. Contributions to Tertiary and Quaternary Geology 31: 15 - 28.", "JaNOSSY, D. 1986. Pleistocene vertebrate faunas of Hungary. Developments in palaeontology and stratigraphy. Vol. 8. Elsevier Press, Amsterdam, The Netherlands.", "MARKOVA, A. K., N. G. SMIMOV, A. V. KOZHARINOV, N. E. KAZANTSEVA, A. N. SIMAKOVA, AND L. M. KITSSEV. 1995. Late Pleistocene distribution and diversity of mammals in northern Eurasia (paleofauna database). Paleontologia I Evolucii 28 - 29: 5 - 143.", "KOLFSCHOTEN, T. Van. 1991. The Saalian mammal fossil from Wageningen- Fransche Kamp. Mededelingen Rijks Geological Dienst 46: 37 - 53.", "DE JONGE, G. 1980. Response to con- and heterospecific male odours by the voles Microtus agrestis, Microtus arvalis and Clethrionomys glareolus with respect to competition for space. Behaviour 73: 277 - 303.", "STODDART, D. M. 1982. Demonstration of olfactory discrimination by the short-tailed vole Microtus agrestis. Animal Behaviour 30: 293 - 294.", "JOHNSON, E. 2008. Moulting cycles. Mammal Review 1: 198 - 208.", "BaUMLER, W. 1979. Die Sommerkrise der Erdmaus (Microtus agrestis L.) Teil I. Die Entwicklungeiner freilebenden Population. Anzeiger Schadlingskde, Pflanzenschutz, Umweltschutz 52: 65 - 70.", "BURTHE, S. J., ET AL. 2010. Individual growth rates in natural field vole Microtus agrestis populations exhibiting cyclic population dynamics. Oecologia 162: 653 - 61.", "FERNS, P. N. 1976. Diet of a Microtus agrestis population in southwest Britain. Oikos 27: 506 - 511.", "PHILLIPSON, J., M. SARRAZIN- COMANS, AND C. STOMATOPOULOS. 1983. Food consumption by Microtus agrestis and the unsuitability of faecal analysis for the determination of food preference. Acta Theriologica 28: 397 - 416.", "HANSSON, L. 1984. Winter reproduction of small mammals in relation to food condition and population dynamics. Special Publication, Carnegie Museum of Natural History 10: 225 - 234.", "MEERLO, P., L. BOOLE, G. H. VISSER, D. MASMAN, AND S. DAAN. 1997. Basal metabolic rate in relation to body composition and daily energy expenditure in the field vole, Microtus agrestis. Physiological Zoology 70: 362 - 369.", "JACKSON, D. M., P. TRAYHURN, AND J. SPEAKMAN. 2001. Associations between energetics and over-winter survival in the short-tailed field vole Microtus agrestis. Journal Animal Ecology 70: 633 - 640.", "MADISON, D. 1985. Activity rhythms and spacing. Pp. 373 - 413 in Biology of new world Microtus (R. H. Tamarin, ed.). Special Publication 8, American Society of Mammalogists, Lawrence, Kansas.", "HAYES, J. P., J. R. SPEAKMAN, AND P. A. RACEY. 1992. The contributions of local heating and reducing exposed surface area to the energetic benefits of huddling by short-tailed field voles (Microtus agrestis). Physiological Zoology 65: 742 - 762.", "KONIG, C. 1973. Mammals. Collins & Co., London, United Kingdom.", "BROWN, A. M. 1973. High frequency peaks in the cochlear microphonic response of rodents. Journal of Comparative Physiology 83: 377 - 392.", "MYLLYMaKI, A. 1977 b. Interspecific competition and home range dynamics in the field vole Microtus agrestis. Oikos 29: 553 - 569.", "ERNEST, S. K. 2003. Life history characteristics of placental non-volant mammals. Ecology 84: 3402.", "ERLINGE, S., J. AGRELL, J. NELSON, AND M. SANDELL. 1990. Social organization and population dynamics in a Microtus agrestis population. Pp. 45 - 58 in Social systems and population cycles in voles (R. Tamarin, R. Ostfeld, S. Pugh, and G. Bujalska, eds.). Birkhauser Verlag, Basel, Switzerland.", "ERGON, T., J. L. MACKINNON, N. C. STENSETH, R. BOONSTRA, AND X. LAMBIN. 2001. Mechanisms for delayed density-dependent reproductive traits in field voles, Microtus agrestis: the importance of inherited environmental effects. Oikos 95: 185 - 197.", "BELDOMENICO, P., S. TELFER, S. GEBERT, L. LUKOMSKI, M. BENNETT, AND M. BEGON. 2008. The dynamics of health in wild field vole: a haematological perspective. Journal Animal Ecology 77: 984 - 997.", "GROCOCK, C. A. 1979. Testis development in the vole, Microtus agrestis, subjected to long or short photoperiods from birth. Journal of Reprodu ction and Fertility 55: 423 - 427.", "ANDERA, M. 1981. Reproduction of Microtus agrestis in Czechoslovakia. Acta Scientarium Naturalium Brno / Prirodoredne' Prace Ustavu Ceskoslovenske Ved v Brne 15: 1 - 38.", "CHARLTON, H. M., S. A. CHIAPPA, G. FINK, C. S. GROCOCK, AND E. VERSI. 1983. Hypothalamic gonadotropin-releasing hormone and pituitary luteinizing hormone contents in the male vole (Microtus agrestis) in the field during breeding and nonbreeding seasons. Canadian Journal of Zoology 61: 2405 - 2410.", "NELSON, J. 1994. Determinants of spacing behaviour, reproductive success and mating system in male field voles, Microtus agrestis. Ph. D. dissertation, Lund University, Lund, Sweden.", "NELSON, J. 1995 a. Determinants of male spacing behavior in microtines: an experimental manipulation of female spatial distribution and density. Behavioral Ecology and Sociobiology 37: 217 - 223.", "MILLIGAN, S. R. 1974. Social environment and ovulation in the vole Microtus agrestis. Journal of Reproduction and Fertility 41: 35 - 37.", "PUSENIUS, J., J. VIITALA, T. MARIENBERG, AND S. RITVANEN. 1998. Matrilineal kin clusters and their effect on reproductive success in the field vole Microtus agrestis. Behavioral Ecology 9: 85 - 92.", "BERTEAUX, D., J. BETY, E. RENGIFO, AND J. M. BERGERON. 1999. Multiple paternity in meador voles (Microtus pennsylvanicus): investigating the role of the female. Behavioral Ecology and Sociobiology 45: 283 - 291.", "CORBET, G. B. 1966. The terrestrial mammals of western Europe. G. T. Foulis and Co. Ltd., London, United Kingdom.", "NELSON, J., J. AGNELL, S. ERLINGE, AND M. SANDELL. 1991. Reproduction of different female age categories and dynamics in a non-cyclic field vole (Microtus agrestis) population. Oikos 61: 73 - 78.", "HANSSON, L. 1987. Vole sex ratios: the importance of mating systems and maternal condition. Oikos 49: 161 - 164.", "CAPLEN, G., T. T. MOTTRAM, A. R. PICKARD, AND S. R. MILLIGAN. 2004. A biosensor-based method for non-invasively monitoring wildlife reproduction-the field vole (Microtus agrestis) as a potential biomarker of environmental disruption. Analytical Letters 37: 1719 - 1735.", "MYLLYMaKI, A. 1977 a. Demographic mechanisms in the fluctuating populations of the field vole, Microtus agrestis. Oikos 29: 468 - 493.", "EBENHARD, T. 1990. A colonization strategy in field voles (Microtus agrestis): reproductive traits and body size. Ecology 71: 1833 - 1848.", "HANSSON, L. 1977. Spatial dynamics of field voles Microtus agrestis in heterogeneous landscapes. Oikos 29: 539 - 544.", "STENSETH, N. C. 1977. On the importance of spatio-temporal heterogeneity for the population dynamics of rodents towards a theoretical foundation for rodent control. Oikos 29: 545 - 552.", "BIERMAN, S. M., J. P. FAIRBAIRN, S. J. PETTY, D. A. ELSTON, D. TIDHAR, AND X. LAMBIN. 2006. Changes over time in the spatiotemporal dynamics of cyclic populations of the field vole (Microtus agrestis). The American Naturalist 167: 583 - 590.", "DALKVIST, T., R. SIBLY, AND C. J. TOPPING. 2011. How predation and landscape fragmentation affect vole population dynamics. PLoS One 6: e 22834.", "HUITU, O., M. KOIVULA, E. KORPIMaKI, T. KLEMOLA, AND K. NORRDAHL. 2003. Winter food supply limits growth of northern vole populations in the absence of predation. Ecology 84: 2108 - 2118.", "MASSEY, F. P., M. J. SMITH, X. LAMBIN, AND S. E. HARTLEY. 2008. Are silica defences in grasses driving vole population cycles? Biology Letters 4: 419 - 422.", "VILLAR, N., T. CORNULIER, D. EVANS, R. PAKEMAN, S. REDPATH, AND X. LAMBIN. 2014. Experimental evidence that livestock grazing intensity affects cyclic vole population regulation processes. Population Ecology 56: 55 - 61.", "WILSON, S. 2008. The development of social behavior in the vole (Microtus agrestis). Zoological Journal of the Linnean Society 52: 45 - 62.", "MYLLYMaKI, A. 1970. Population ecology and its application to the control of the field vole, Microtus agrestis (L.). European and Mediterranean Plant Protection Organization Publications, Serie A 58: 27 - 48.", "GOUVEIA, A., ET AL. 2015. Long-term pattern of population dynamics in the field vole from central Europe: cyclic pattern with amplitude dampening. Population Ecology 57: 581 - 589.", "MYLLYMaKI, A. 1977 c. Outbreaks and Damage by the Field Vole, Microtus agrestis (L.), since World War II in Europe. EPPO Bulletin 7: 177 - 207.", "RASMUSON, B., M. RASMUSON, AND J. NYGREN. 1977. Genetically controlled differences between cycling and non-cycling populations of field vole (Microtus agrestis). Hereditas 87: 33 - 41.", "REINWALDT, E. 1968. Sum Kauflachenmuster der molaraen der erdmaus (Microtus agrestis Linne) in Schweden. Arkiv for Zoologia 20: 495 - 500.", "NYGREN, J. 1980 a. Allozyme variation in natural populations of field vole (Microtus agrestis L.). I. Survey of the \" semistable \" population in southern Sweden. Hereditas 92: 65 - 72.", "NYGREN, J. 1980 b. Allozyme variation in natural populations of field vole (Microtus agrestis L.). II. Survey of an isolated island population. Hereditas 93: 107 - 123.", "STENSETH, N. C., T. O. GUSTAFSSON, L. HANSSON, AND K. I. UGLAND. 1985. On the evolution of reproductive rates in microtine rodents. Ecology 66: 1795 - 1808.", "SAVOLA, S., H. HENTTONEN, AND H. LINDeN. 2013. Vole population dynamics during succession of a commercial forest in northern Finland. Annals Zoologici Fennici 50: 79 - 88.", "MARCHI, C., L. W. ANDERSEN, C. DAMGAARD, K. OLSEN, T. S. JENSEN, AND V. LOESCHCKE. 2013. Gene flow and population structure of a common agricultural wild species (Microtus agrestis) under different land management regimes. Heredity 111: 486 - 494.", "LOUGHRAN, M. F. 2007. Social organization of the male field vole Microtus agrestis: a case of transient territoriality? Annales Zoologici Fenni